PENGARUH TINGKAT KESEJAHTERAAN TERHADAP KINERJA KARYAWAN PADA PT ANDRITZ PULP AND PAPER DI PASIR PUTIH - Yusnika, Arni; ', Makhdalena; ', RM.Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted to test the influence of the welfare of the performance of employees PT Andritz Pulp and Paper. The population in this study are employees of PT Andritz as much as 30 people. The type of data used is primary data. Data analysis technique using regression, with 6,058 + 0,646 welfare + e. Furthermore the determination R2 variabel independet give influence of 29,9% and residue 70,1 % influenced by other factors in this study.Keywords: Performance , Welfare